Kerala: The Dilemmas of Equality in Higher Education - Altbach, Philip; Mathews, Eldho (International Higher Education, 2010)
The system of higher education in the state of Kerala, on India's southwest coast, has developed under unique social and political circumstances. Kerala is by most educationally measures the most advanced state in India. Its current government is a coalition dominated by the Marxist Communist Party of India. The state's higher education future is complex but practical. Careful attention needs to be given to the organization of the higher education system.